Representaciones rupestres de barcos mediterráneos en relación con el paleopaisaje costero gaditano (Cádiz, sur de España) - Samaniego Bordiú, Blanca (Complutum, 2007)
The implication of the Shelter of Laja Alta (Jimena de la Frontera, Cádiz), where they appear the rock representations of boats, with the coast has been settled down through visual control on the Bay of Algeciras and through of navigation by the Guadiaro river. Both forms of relation are based on the interpretation of the symbolic registry. The geomorphologyc study of this holocene estuarine river basin and its recent deltaic evolution allows us to confirm and to clarify the active paper of this communication channel between the mountain interior and paleocosta, reconstructed this one like result of the investigation. In chronological terms this paleocoast comprises of the scene of the rock representations: its morphology was stable in the heat of Bronze Age and stays in the beginnings of the Iron Age until V century a.C.